SELECTION OF THE BEST LOCATIONS OF NEW PHOTOVOLTAIC FARMS IN JORDAN USING GIS - Mohammed Taleb Obaidat; Nour Abu Shuaib (Jadara Journal of Social Sciences, 2020)
The aim of this study were to determine of best areas to construct new photovoltaic farms in Jordan using four main factors that majorly affect the feasibility of these farms which is solar radiation yearly sum on the land, aspect of the land, height of the land and the presence of electricity lines near the land. Further, to represent main current projects in Geographic Information Systems (GIS) software. The outcome results will produce a map of Jordan Suitability areas to construct new Photovoltaic farms by using GIS software and many calculations with remote sensing techniques and represent some of the current main photovoltaic projects on it as a spatial data with their names and their capacities. The new methodology will open the door for numerous GIS applications in the area of Solar Energy.